The potential cost-effectiveness of the Diamondback 360® Coronary Orbital Atherectomy System for treating de novo, severely calcified coronary lesions: an economic modeling approach. (April 2016) - Chambers, Jeffrey; Généreux, Philippe; Lee, Arthur; Lewin, Jack; Young, Christopher; Crittendon, Janna; Mann, Marita; Garrison, Louis P.
Background: Patients who undergo percutaneous coronary intervention (PCI) for severely calcified coronary lesions have long been known to have worse clinical and economic outcomes than patients with no or mildly calcified lesions. We sought to assess the likely cost-effectiveness of using the Diamondback 360 ® Orbital Atherectomy System (OAS) in the treatment of de novo, severely calcified lesions from a health-system perspective. Methods and results: In the absence of a head-to-head trial and long-term follow up, cost-effectiveness was based on a modeled synthesis of clinical and economic data. A cost-effectiveness model was used to project the likely economic impact. To estimate the net cost impact, the cost of using the OAS technology in elderly (⩾ 65 years) Medicare patients with de novo severely calcified lesions was compared with cost offsets. Elderly OAS patients from the ORBIT II trial (Evaluate the Safety and Efficacy of OAS in Treating Severely Calcified Coronary Lesions) [ClinicalTrials.gov identifier: NCT01092426] were indirectly compared with similar patients using observational data. For the index procedure, the comparison was with Medicare data, and for both revascularization and cardiac death in the following year, the comparison was with a pooled analysis of the Harmonizing Outcomes with Revascularization and Stents in Acute Myocardial Infarction (HORIZONS-AMI)/Acute Catheterization and Urgent Intervention Triage Strategy (ACUITY) trials. After adjusting for differences in age, gender, and comorbidities, the ORBIT II mean index procedure costs were 17% ( p < 0.001) lower, approximately US2700. Estimated mean revascularization costs were lower by US1240 in the base case. These cost offsets in the first year, on average, fully cover the cost of the device with an additional 1.2% cost savings. Even in the low-value scenario, the use of the OAS is cost-effective with a cost per life-year gained of US11, 895. Conclusions: Based on economic modeling, the recently approved coronary OAS device is projected to be highly cost-effective for patients who undergo PCI for severely calcified lesions.